Fabrication of Silver Interdigitated Electrode by a Stamp Method - Kan-Sen Chou; Chia-Hsuan Lee (Advances in Materials Science and Engineering)
A stamp method was developed in this study to fabricate interdigitated electrodes (IDEs) on glass substrate from a 37.5 wt% silver ink. This method is simple and fast. A small amount of silver ink was first dripped into an IDE-patterned sponge of a stamp and then one could stamp out the desired IDE pattern made of nanosized silver colloids on a glass substrate, which was subsequently sintered at 280°C for 10 minutes to obtain the final silver IDE. Our brief study showed that when a large stamping force was used, more ink would be stamped out in the beginning and it decreased after each usage. However, if the force was too small, there would not be sufficient ink for a complete IDE. There existed therefore an optimal force to fabricate IDEs with minimal changes from sample to sample. The average dimension of an IDE when the applied force was 102 gm was roughly 403 ± 20 µm in width and 1154 ± 153 nm in height, and the average final electrical resistivity was about 10×10-6 Ω-cm.